2021
DOI: 10.17245/jdapm.2021.21.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of headache intensity and frequency with maxillary stabilization splint therapy in patients with temporomandibular disorders-headache comorbidity: a systematic review and meta-analysis

Abstract: This systematic review and meta-analysis aimed to analyze the effectiveness of maxillary stabilization splint (SS) therapy to reduce headache (HA) intensity and HA frequency in patients with temporomandibular disorders (TMD)-HA comorbidity. Randomized controlled trials (RCTs) using full-arch coverage, hard resin, and maxillary SS therapy were included. Electronic databases, including Cochrane Library, MEDLINE through PubMed, Web of Science, and EMBASE, were searched. The risk of bias was analyzed based on Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Individuals with TMDs are susceptible to migraines and tension-type headaches ( Saha et al, 2019 ). Several studies have been conducted to understand the relationship between headaches and TMDs to conclude that temporomandibular disorders are the second most common cause of musculoskeletal discomfort and that tension-type headaches are strongly associated with TMDs ( Kostrzewa-Janicka et al, 2013 , Manrriquez et al, 2021 ). In addition to the increasing prevalence of chronic headaches, TMDs can exacerbate primary headaches ( Saha et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with TMDs are susceptible to migraines and tension-type headaches ( Saha et al, 2019 ). Several studies have been conducted to understand the relationship between headaches and TMDs to conclude that temporomandibular disorders are the second most common cause of musculoskeletal discomfort and that tension-type headaches are strongly associated with TMDs ( Kostrzewa-Janicka et al, 2013 , Manrriquez et al, 2021 ). In addition to the increasing prevalence of chronic headaches, TMDs can exacerbate primary headaches ( Saha et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study examining the association between TMD treatment and their influence on headache treatment found that the treatment of TMDs greatly reduced headache frequency and intensity ( Costa et al, 2015 ). Several studies and strong evidence suggest that occlusal splint therapy for TMDs may help to treat and reduce migraine and tension-type headaches ( Cooper and Kleinberg, 2009 , Costa et al, 2015 , D’Ermes et al, 2012 , Kostrzewa-Janicka et al, 2013 , Manrriquez et al, 2021 , Quayle et al, 1990 , Saha et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the use of stabilization splints, both soft and hard, has been demonstrated in various scientific reports. Stabilization splint therapy has been described as a well-established treatment for TMDs [ 10 , 11 ], bruxism [ 12 , 13 ], and headache [ 14 ]. Soft stabilization splints are effective in the symptomatic management of TMDs, especially for symptoms such as temporomandibular joint (TMJ) clicking, TMJ pain, and masticatory muscle pain [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manrriquez et al ( 23 ), in a systematic review and meta-analysis, demonstrated that SSs induces a reduction of headache intensity or frequency in patients with TMD headache comorbidity. However, the evidence quality in this study was low, with only nine studies being analyzed in the qualitative synthesis and five studies in the quantitative synthesis (meta-analysis).…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence quality in this study was low, with only nine studies being analyzed in the qualitative synthesis and five studies in the quantitative synthesis (meta-analysis). However, the authors reported no significant difference in the use of partial hard or soft splints or full arch splint use ( 23 ). A recent review investigating the effects of a SSs on headaches in patients with TMDs, revealed that even though SS therapy reduced headache intensity and frequency, the evidence quality was inadequate due to the high bias risk and small sample size, which indicated that there is a need for more research ( 23 ).…”
Section: Introductionmentioning
confidence: 99%